Integritas Artificial Intelligence dalam Pembelajaran Sejarah untuk Meningkatkan Literasi Sejarah Digital Peserta Didik - Istiqomah Istiqomah; Sifana Alqorana; Meysi Wulandari; Safina Desfianti; Sani Safitri (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
The rapid development of digital technology in the 21st century has brought significant changes to various aspects of life, including education. One of the emerging innovations in the educational field is the use of Artificial Intelligence (AI) as a tool to support the learning process. The integration of AI in history education offers new opportunities to create more interactive, adaptive, and contextual learning experiences through access to various digital historical sources. This study aims to analyze the integration of Artificial Intelligence in history learning and its implications for improving students’ digital historical literacy. This research uses a qualitative approach with a descriptive method through a literature study by reviewing various scientific articles related to the use of AI in education and digital literacy in history learning. The findings indicate that the use of Artificial Intelligence can assist students in accessing, analyzing, and understanding various digital historical sources more broadly through interactive media such as online archives, historical simulations, and technology-based learning platforms. In addition, the integration of AI can increase student engagement in the learning process, encourage critical thinking skills, and support more personalized learning based on students’ needs and abilities. However, the implementation of this technology must be accompanied by the strengthening of digital historical literacy as well as the application of academic integrity, ethical principles, and responsible use of technology. Therefore, the proper integration of Artificial Intelligence can serve as an innovative strategy to enhance the quality of history education in the digital era.